The Safety and Efficacy of Botanicals with Nootropic Effects - Roe, Amy L.; Venkataraman, Arvind (Current Neuropharmacology, 2021)
Recent estimates for the global brain health supplement category, i.e. nootropic market size, will grow to nearly 5.8 billion by 2023. Overall, nearly one-quarter (23%) of adults currently take a supplement to maintain or improve brain health or delay and reverse dementia. Not surprisingly, the use of such supplements increases with age - more than one-third of the oldest generation (ages 74 and older) takes a supplement for brain health. This widespread use is being driven by a strong desire both in the younger and older generations to enhance cognitive performance and achieve healthy aging. The most prevalent botanicals currently dominating the nootropic marketplace include Gingko biloba, American ginseng, and Bacopa monnieri. However, other botanicals that affect stress, focus, attention, and sleep have also been procured by dietary supplement companies developing products for improving both, short and long-term brain health. This review focuses on efficacy data for neuroactive botanicals targeted at improving cognitive function, stress reduction, memory, mood, attention, concentration, focus, and alertness, including Bacopa monnieri, Ginkgo biloba, Holy basil, American ginseng, Gotu kola, Lemon balm, Common and Spanish sages and spearmint. Botanicals are discussed in terms of available clinical efficacy data and current safety profiles. Data gaps are highlighted for both efficacy and safety to bring attention to unmet needs and future research.
Keywords: cognition